Efektivitas Pengelolaan Dana Kelurahan dalam Rangka Peningkatan Sarana dan Prasarana dan Kesejahteraan Masyarakat di Kelurahan Dukuh Menanggal Kecamatan Gayungan Kota Surabaya - Muh. Rizal Khoirudin; Muhammad Sandi Arifianto; Shiva Siti Iklimah Ariyanti; Revalina Nur Izzah; Juwita Nur Fadila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effectiveness of urban village fund management in efforts to improve facilities and infrastructure as well as community welfare in Dukuh Menanggal Village, Gayungan Subdistrict, Surabaya City. Urban village funds are part of a fiscal decentralization policy that aims to accelerate development and equitable distribution of welfare at the local level. This research uses descriptive qualitative methods with data collection techniques through observation, in-depth interviews, and documentation. The results showed that the management of urban village funds in Dukuh Menanggal has generally been quite effective, marked by an improvement in the quality of environmental infrastructure such as roads, drains, and other public facilities. In addition, some community empowerment programs also have a positive impact on improving the welfare of residents. However, there are still some obstacles such as limited apparatus capacity, suboptimal community participation, and transparency in reporting that need to be improved. Therefore, it is necessary to strengthen governance, increase the capacity of human resources, and involve the community more actively so that the management of urban village funds can be more optimal and sustainable.